Pengaruh Kualitas Produk Dan Promosi Penjualan Terhadap Keputusan Pembelian: Studi Kasus Pada Café Story House Di Kota Bogor - Indah, Imelda Frizellia; Gendalasari, Gen Gen (Jurnal Ilmiah Pariwisata Kesatuan, 2023)
This study aims to: (1) To determine the effect of Product Quality on Purchasing Decisions, (2) To determine the effect of Sales Promotion on Purchasing Decisions, (3) To determine the effect between the quality of Sales Promotion products on Purchasing Decisions. The number of samples was 385 respondents using the Cochran Formula formula. The data analysis method used is linear regression analysis to determine the Effect of Product Quality and Sales Promotion on Purchasing Decisions at Cafe Story House in Bogor City. Data testing is performed using Software Statistical Package For The Social Sciencer (SPSS) software. Based on the test results, the following data were obtained: (1) there is an influence of Product Quality on Purchasing Decisions showing significant results (2) there is an influence of Sales Promotion on Purchasing Decisions showing significant results (3) There is an influence between Product Quality and Sales Promotion on Purchasing Decisions showing significant results Keywords : Product Quality, Sales Promotion, Purchase Decision